2019
DOI: 10.14202/vetworld.2019.325-330
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of two-dimensional mode and color Doppler sonography in predicting gender of the equine fetus

Abstract: Background and Aim: Ultrasonographic fetal sexing is of utmost economic importance for horse breeders. Relatively, a few studies have been conducted to determine fetal sex in mare using transrectal Doppler ultrasound. This study aimed to compare two sexing techniques, two-dimensional (2D) mode and color Doppler ultrasonography. Materials and Methods: The study was conducted on 39 mares under field conditions. Examinations were performed using the ultrasonic model device (Medison SonoAce Pico, South Korea), eq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Determination of equine fetal sex during mid‐gestation (90–150 days) using a B‐mode scan is based on the identification of fetal gonads and external genitalia (Bucca, 2005). Recent reports have demonstrated that colour Doppler ultrasonography combined with B‐mode ultrasonography provided greater accuracy in the diagnosis of fetal sex in both periods (mid and late‐gestation), allowing better visualization of the fetal gonads, especially in males (Mebarki et al, 2019; Resende et al, 2014) (Figure 4). The assessment of vascularization of the gonads using colour Doppler is a helpful tool for the non‐experienced practitioner for sexing of the fetus between 120 and 150 days.…”
Section: New Applications Of Doppler Ultrasound In Maresmentioning
confidence: 99%
“…Determination of equine fetal sex during mid‐gestation (90–150 days) using a B‐mode scan is based on the identification of fetal gonads and external genitalia (Bucca, 2005). Recent reports have demonstrated that colour Doppler ultrasonography combined with B‐mode ultrasonography provided greater accuracy in the diagnosis of fetal sex in both periods (mid and late‐gestation), allowing better visualization of the fetal gonads, especially in males (Mebarki et al, 2019; Resende et al, 2014) (Figure 4). The assessment of vascularization of the gonads using colour Doppler is a helpful tool for the non‐experienced practitioner for sexing of the fetus between 120 and 150 days.…”
Section: New Applications Of Doppler Ultrasound In Maresmentioning
confidence: 99%
“…In the early stage of pregnancy of mare, particularly before 70 days, the estimation of the size and the asymmetry of uterus by transrectal palpation (Ginther, 1983) and some ultrasound measurements on the fetus can be used for determining gestational age (Acker et al, 2001;Ginther, 2007). Between 70 and 90 days, the fetus sinks into the abdominal cavity and becomes no longer explorable (Bucca, 2005;Mebarki et al, 2019). After 90 days of gestation, ultrasound measurements of fetal ocular orbit are an easy technic, widely used to determine gestational age (Renaudin et al, 2000;Turner et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…This formula was integrated in several ultrasound machines, as a reference formula. However, this formula could not provide the accurate gestation age for other breeds owing the genetic and morphological variations between breeds (Hevia et al, 1994;Mebarki et al, 2019;Panchal and Gujarati 1995). In this context, Hartwig et al (2013) found a divergence in fetal orbit measurements between Crioulo horse and those of Thoroughbred of similar size (Hartwig et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…During this period, it is important to notice that there is a transition period characterized by delayed ovulation, andmares are not at their optimal reproductive potential (Handler et al, 2007). Moreover, mare breeders want foals born as soon as possible after the first of January (Mebarki et al, 2019), because, in the racing world, foals and yearlings are put into competition according to their year of birth. Moreover, anoestrus seasonality in the mare limits reproduction for a variable period.…”
Section: Introductionmentioning
confidence: 99%